2011
DOI: 10.1007/s10522-011-9367-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of age-associated neurodegeneration and promotion of healthy brain ageing in female Wistar rats by long term use of bacosides

Abstract: Bacopa monnieri (L.), popularly known as Brahmi, is a revered Ayurvedic medicinal plant used as nerve tonic since time immemorial. The present study aims to investigate the neuroprotective effect of bacosides, the active saponins of Bacopa monnieri (L.) against age associated neurodegeneration and its impact over the prevention of Senile Dementia of Alzheimer's Type (SDAT). The optimum dose of bacosides with no adverse effect was selected by screening its dose dependant activity on ageing biomarker lipofuscin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 51 publications
(38 reference statements)
1
43
0
Order By: Relevance
“…During ageing (Rastogi et al 2012) and ovariectomy (Martins et al 2012), the enhanced generation of ROS induced chronic oxidative stress in the brain. This condition caused gradual accumulation of damaged proteins leading to a functional decline in the brain's endogenous defence system (Rumora et al 2007;Min et al 2008) and leading to the activation of stress kinases (JNK and p38 MAPK) (Gabai et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…During ageing (Rastogi et al 2012) and ovariectomy (Martins et al 2012), the enhanced generation of ROS induced chronic oxidative stress in the brain. This condition caused gradual accumulation of damaged proteins leading to a functional decline in the brain's endogenous defence system (Rumora et al 2007;Min et al 2008) and leading to the activation of stress kinases (JNK and p38 MAPK) (Gabai et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to bacoside A and bromelain both along with dichlorvos increased the activities of AChE and BChE which implies that bacoside A and bromelain have the property to boost up the cholinergic system. Bacoside A increases AChE activity in aged rat brain cortex and the middle aged (Rastogi et al 2012). After dichlorvos exposure, the level of GABA declined.…”
Section: Discussionmentioning
confidence: 92%
“…Exposure to bacoside A and bromelain separately and both along with dichlorvos increased the GABA and decreased the serotonin activity. In a previous study, Rastogi et al (2012) reported that bacoside A prevents the loss of serotonin and dopamine content. Bacoside A increased the GABA receptor in epileptic mice (Mathew et al 2009).…”
Section: Discussionmentioning
confidence: 94%
“…45 Several preclinical analysis and clinical trials have proven the efficacy of these plants in management of cognitive deficits in aged population. 16,43,[46][47][48][49][50] Subsequently, metformin in addition to its antidiabtic properties has been also recently recognized as a potential treatment for neurodegenerative disorders such as AD. Studies have shown that metformin prevents apoptotic cascade in endothelial cell type by inhibiting Permeability Transition Pore (PTP) and blocking the release of cytochrome-c that will lead to cell death.…”
Section: Discussionmentioning
confidence: 99%